Primary Liposarcoma of the Mediastinum. (1998) - Greif, Joel; Marmor, Silvia; Merimsky, Ofer; Kovner, Felix; Inbar, Moshe
Abstract : Patient. A 62-year-old man presented with effort dyspnea, non-productive cough and weakness of 4 month duration. He had no findings on physical examination. Discussion. Chest X-ray revealed a large mass in the left anterior mediastinum. Computerized tomography of the chest showed a well-delineated homogeneous mediastinal mass with fat-equivalent density and a small pleural effusion. Fiberoptic bronchoscopy revealed narrowing of the left main bronchus, secondary to external compression. The bronchial mucosa was normal and brush cytology was negative. A CT-guided fine needle aspiration (FNA) of the mass yielded fragments of cells embedded in myxoid background material and closely packed atypical lipoblasts, compatible with liposarcoma. The patient underwent a left lateral thoracotomy and margibnal resection of the mass. The histopathological examination confirmed the diagnosis of mixed-type liposarcoma, consisted of myxoid and pleomorphic liposarcoma. Postoperative two-field radiation therapy was delivered to the mediastinum for a total midplane dose of 40 Gy. After a disease-free interval of 8 months the disease recurred in the mediastinum and pleura. Palliative chemotherapy achieved a short duration partial response but the patient succumbed to local recurrence 2 years after the diagnosis.